Determinants of house price in Malaysia / Muhammad Taufiqur Rahman Musak - Musak, Muhammad Taufiqur Rahman (2024)
This study is aim to find out determinants of house price in Malaysia. In order to measure the house price in Malaysia, some of determinants are being used to see its influence towards the house price. Testing and analysing data that have collected can be done by using interactive software E-View. The determinants are inflation rate (IR), lending interest rate (RR), Gross Domestic Production (GDP), and population (PP). The study is being done to investigate and examine the volatility of house price in Malaysia over a year of 1989 till 2012. Most of previous research papers are more focusing in understand the essential of house investing and the government policies. This study showed how the house investors and the government policy gave implication to estimate the condition of variance of house market price with the respect of its volatility over the time. Moreover, the important of considering the sub-national factors in formulating the national house policy should be address by the government. The analysis and result of this research paper are limited by quality of the data. Thus this paper would provide us with the result of indicated view and determinants that affecting volatility of house price in Malaysia.